Effects of Different Matrices on the Analysis of Oligosaccharides and Polysaccharides by Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry - ZHANG Zihao, WANG Junqiao, NIE Shaoping (Shipin Kexue, 2025)
In this study, the effects of binary matrices (amino-4-hydroxybenzoic acid (AHB)/2,5-dihydroxybenzoic acid (DHB), 3-hydroxycoumarin (3-HC)/DHB), ionic liquid matrices (N,N-dimethylaniline (DMA)/DHB, 2-(p-hydroxybenzene-azo)benzoic acid (HABA)/1,1,3,3-tetramethylguanidine (TMG), 4-hydroxycoumaric acid (CA)/TMG, 2,4,6-trihydroxyacetophenone (THAP)/TMG, N-methylaniline (NMA)/DHB) and reactive matrices (3-hydrazylbenzoic acid (3-HBA)/DHB, 6-hydrazine niacin (HYNIC)/DHB, 2-hydrazopyridine (2-HPM)) on the analysis of maltooctaose, trigalacturonic acid and dextran T6 by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) were studied and compared with those of three solid matrices (DHB, THAP, α-cyano-4-hydroxycinnamic acid). The effects of various matrix solvents on the detection of maltoocatose as an oligosaccharide were studied. Meanwhile, the effects of solvent, reaction time and reaction temperature on the derivatization rate were addressed using reactive matrices. Results showed that all three matrices exhibited good detection performance for maltooctalose with good spectral reproducibility and increased peak intensity. Using the reactive substrates, the derivatization temperature was at least 65 ℃. 2-HPM had high derivatization efficiency, up to (96.28 ± 0.28)%, under all conditions, and using this reactive substrate, the derivatization reaction could be completed within a short period of time (15 min), but the derivatization rate was not high. While the signal-to-noise ratios of 3-HBA/DHB and HYNIC/DHB derived oligosaccharides were high, their derivatization rates were relatively low with a reaction time of at least 60 min. In addition, the concentration of oligosaccharides had a significant effect on the derivatization efficiency; when the concentration was less than 108 fmol/L, the derivatization signal was very low or undetected. The m/z signal of tri-galacturonic acid was significantly higher when using THAP and 3-HBA/DHB compared to other matrices. For dextran T6, both binary and ionic liquid matrices exhibited better detection performance, and AHB/DHB, 3-HC/DHB, THAP/TMG, and NMA/DHB could be used to detect a wider range of molecular mass, including polysaccharides with a polymerization degree of up to 36. The results of this study provide a reference for the analysis and identification of carbohydrates.